2013
DOI: 10.1152/ajprenal.00231.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of diuretic stimulation of an insect secretory epithelium by a cGMP-dependent protein kinase

Abstract: The rate of urine secretion by insect Malpighian tubules (MTs) is regulated by multiple diuretic and antidiuretic hormones, often working either synergistically or antagonistically. In the Drosophila melanogaster MT, only diuretic factors have been reported. Two such agents are the biogenic amine tyramine (TA) and the peptide drosokinin (DK), both of which act on the stellate cells of the tubule to increase transepithelial chloride conductance. In the current study, TA and DK signaling was quantified by microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…5). In D. melanogaster, cGMP was shown to inhibit depolarization induced in kinin-stimulated MTs, suggesting an anti-diuretic effect (Ruka et al, 2013) as fluid secretion rates were not directly measured. Thus, in agreement with observations made in another dipteran insect, our results support the presence of an additional anti-diuretic hormone that signals through cGMP and reduces the activity of diuretic factors targeting stellate cells (Ruka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). In D. melanogaster, cGMP was shown to inhibit depolarization induced in kinin-stimulated MTs, suggesting an anti-diuretic effect (Ruka et al, 2013) as fluid secretion rates were not directly measured. Thus, in agreement with observations made in another dipteran insect, our results support the presence of an additional anti-diuretic hormone that signals through cGMP and reduces the activity of diuretic factors targeting stellate cells (Ruka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, both these second messengers have been shown to lead to stimulation of diuresis in D. melanogaster principal cells (Davies et al, 1995;Kean et al, 2002;Kerr et al, 2004). In stellate cells, cGMP signalling was shown to stimulate diuresis following activation of the mammalian atrial natriuretic peptide receptor expressed specifically in stellate cells (Kerr et al, 2004), while it was inferred to have an anti-diuretic effect on kinin-stimulated MTs (Ruka et al, 2013). Nonetheless, as the natriuretic activity of DromeDH 31 is unaffected in response to AedaeCAPA-1, it is possible that the inhibitory mechanism differs somewhat to that in R. prolixus, where diuretic hormone-induced natriuresis is attenuated by the endogenous CAPA peptide (Paluzzi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…cAMP and cGMP have been shown to play a role in stellate cells (Kerr et al, 2004), although the endogenous pathways for cAMP and cGMP are not known for this tubule cell type. Recent research, however, has demonstrated that cGMP acting through DG1 (but not DG2) can inhibit transepithelial responses induced by both tyramine and D. melanogaster leucokinin (Ruka et al, 2013), both of which increase calcium signalling and chloride conductance (Blumenthal, 2003;Cabrero et al, 2013;O'Donnell et al, 1996;Radford et al, 2004;Terhzaz et al, 1999). Thus, a yet-unidentified inhibitory process for tyramine and D. melanogaster leucokinin signalling in stellate cells is cGMP/DG1-mediated.…”
Section: Camp Signallingmentioning
confidence: 99%
“…Interestingly, the inhibition of both DH 31 - and 5-HT stimulated diuresis by Aedae CAPA-1 and cGMP were sensitive to the PKG inhibitor, KT5823, which indicates that while some differences in signalling associated with inhibition of different diuretic hormones may occur, these inhibitory pathways likely converge and involve cGMP activating protein kinase G. Taken together, the findings in this study provide definitive evidence that CAPA peptides are anti-diuretic hormones in the mosquito A. aegypti , which inhibit fluid secretion of adult mosquito MTs through a signalling cascade involving the NOS/cGMP/PKG pathway. Further studies are necessary in mosquitoes as well as other insects to elucidate the differential regulation by DHs and ADHs given ample data supporting that cGMP and related effectors can be both stimulatory 44,79,99,101 and inhibitory 31,32, 36–37,43,81,102 in their control on insect MTs. In conclusion, we have established an anti-diuretic hormone system in the adult mosquito A. aegypti providing evidence of a neural-renal axis whereby the neuropeptidergic anti-diuretic hormone is released by the abdominal segmental neurohaemal organs and subsequently targets their cognate receptor expressed within the principal cells of the MTs to counteract the activity of a subset of mosquito diuretic hormones.…”
Section: Discussionmentioning
confidence: 99%